ANALISIS LIQUIDITY CREATION PADA PERBANKAN DI INDONESIA TAHUN 2007-2013 (STUDI KASUS PADA 10 BANK BESAR DI INDONESIA TAHUN 2013) - Mirajudin, Muhammad; Prasetiono, Prasetiono (Diponegoro Journal of Management, 2015)
Problems related to banking in Indonesia today is the problem of liquidity. It is shown from a commercial bank credit grew 23.03% but not matched by growth in deposits which only reached 16.56% in 2012 (Report of Banking Supervision, 2012). Therefore, this study aims to determine the liquidity creation in Indonesia as well as to analyze the influence of bank capital, credit risk and income instability towards liquidity creation. The samples includes 10 major banks in Indonesia with total assets of more than Rp120billionÂ  in 2013. The reason for choosing this sample because of the 10 largest banks reflects the state of the banks in Indonesia which accounted for 65.2% of total assets, 65.6% of total loans, and 66% of total deposits or deposits in the banking industry (PEFINDO, 2014). The results of this research note that the bank's capital and earnings volatility is significant negative effect on liquidity creation. While the credit risk of a negative but insignificant effect on liquidity creation. In the determination coefficient test showed that 43.6% dependent variable is the liquidity creation can be explained by the independent variable is the capital of banks, credit risk and earnings volatility. While 56.4% is explained by other variables outside the model of this study